PET Radiopharmaceuticals in Brazil and Belarus: Economic Comparison using the case of 18FDG - Brinkevich, Sviatoslav; Pires, Leonardo P.; Portilho, Filipe Leal; Santos-Oliveira, Ralph (Current Radiopharmaceuticals, 2018)
Background: The production of radiopharmaceuticals, especially the PET ones, is a complex combination of economic and social factors. Despite the social aspects, that are essential, the economic issue must be considered and play an important parameter for the implementation and maintenance of producer centers around the world, with especial regards for countries which face economic crisis and/or belongs to aegis of under development countries. Objectives: In order to evaluate this scenario with carried out this study, comparing a well-established producer center in Brazil and a new on in Belarus. Results: The results showed that the producer center in Brazil face serious economic problems and all the production logistic must be re-done. On the other hand the new producer center in Belarus started following a new model of production and although it has not been profitable, the perspectives seem to be better than the Brazilian producer center. Conclusion: The Brazilian model for PET radiopharmaceutical productions should be revised in order to avoid waste and create a new perspective for the research area.
Keywords: PET radiopharmaceuticals